2013
DOI: 10.1063/1.4794750
|View full text |Cite
|
Sign up to set email alerts
|

On thermodynamics in the primary power conversion of oscillating water column wave energy converters

Abstract: Type of publicationArticle (peer-reviewed) The paper presents an investigation to the thermodynamics of the air flow in the air chamber for the oscillating water column wave energy converters, in which the oscillating water surface in the water column pressurizes or de-pressurises the air in the chamber. To study the thermodynamics and the compressibility of the air in the chamber, a method is developed in this research: the power take-off is replaced with an accepted semi-empirical relationship between the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…It is found that the adiabatic index depends linearly on temperature and pressure. The real gas theory has also been applied to the hypothetical OWC device 405 proposed by Sheng et al (2013), obtaining modified expressions for inhalation and exhalation of the air flow. It is shown that differences between the ideal and real gas models can reach 6%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that the adiabatic index depends linearly on temperature and pressure. The real gas theory has also been applied to the hypothetical OWC device 405 proposed by Sheng et al (2013), obtaining modified expressions for inhalation and exhalation of the air flow. It is shown that differences between the ideal and real gas models can reach 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Even when the assumption that the process is adiabatic appears totally justified (see e.g. Falcão & Justino (1999) and Sheng et al (2013)), local temperature and 45 moisture conditions might cause deviation from the polytropic ideal gas model. In fact, air confined inside the chamber and surrounding the OWC is a mixture of dry air and water vapour under ambient sea conditions.…”
mentioning
confidence: 99%
See 3 more Smart Citations